Floral anatomy and evolution of pollination syndromes in Lepanthes and close relatives - Bogarín Chaves, Diego Gerardo (2019)
Pleurothallidinae is the largest Neotropical orchid subtribe encompassing >5100 species that are mainly dipteran-pollinated. Various pollination syndromes, targeting hump-backed flies (Phoridae), fungal gnats (Sciaridae), and vinegar flies (Drosophilidae) have been documented in detail for Acianthera, Dracula, Lepanthes, Octomeria, Pleurothallis, and Specklinia, all belonging to different clades. Among them, the highly diverse genus Lepanthes, including about 25% of the species of the Pleurothallidinae, is most closely related to Anathallis, Draconanthes, Frondaria, Lankesteriana, Lepanthopsis, Trichosalpinx, and Zootrophion. Members of this “Lepanthes clade” display high floral divergence and are likely adapted to different pollinators . However, only two pollination studies have been published for the group: one for Lepanthes, pollinated by Bradysia (fungal gnats) and another for Trichosalpinx, pollinated by Forcipomyia (biting midges). Floral traits present in Trichosalpinx, such as purple flowers and a mobile, pubescent lip, evolved to accommodate pollination by biting midges. These traits are also found in other plant species pollinated by biting midges such as Bulbophyllum, Ceropegia spp. (Asclepiadaceae), and Theobroma cacao (Malvaceae). Because some members of the Lepanthes clade exhibit similar floral traits, we hypothesize that pollination by biting midges evolved in these orchids as well. In this study, we discuss the micromorphological and histochemical features of the flowers among some of the members of the Lepanthes clade in order to test the hypothesis on floral convergence in plants pollinated by biting midges and also which other pollination strategies can be inferred from flower anatomy in the sister genera. Based on histochemistry, LM, and SEM we found similar floral secretions such as carbohydrates, proteins, and lipids in different organs of Anathallis, Lankesteriana, and Trichosalpinx, supporting the hypothesis of floral parallelism in these genera. Lepanthopsis with a papillose lip and secretory glenion and Zootrophion with closing flowers and verrucose-papillose inner surface of sepals might employ different pollination systems. This study provides additional micromorphological and histochemical data to support future pollination studies of other members of the Lepanthes clade.